2001
DOI: 10.1002/1521-3951(200103)224:1<291::aid-pssb291>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Luminescence Quantum Efficiency of Nanocrystalline ZnS:Mn2+

Abstract: The influence of the Mn 2+ concentration, the nature of the passivating polymer and UV irradiation on the luminescence efficiency of nanocrystalline ZnS : Mn 2+ is investigated. With increasing Mn 2+ concentration the quantum efficiency increases, until it reaches a stable value. No drastic decrease in quantum efficiency is observed at high Mn 2+ concentrations, as was found earlier for both bulk and nanocrystalline ZnS : Mn 2+ . By altering the passivating polymer many other factors influencing the quantum ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 10 publications
0
17
1
Order By: Relevance
“…The radius of the ZnS nanoparticles before the irradiation was calculated to be 2.97 nm and after the irradiation the radius was reduced to 2.36 nm. This indicates that the irradiation resulted in the decreasing of the nanoparticles, as was reported by Bol et al [24], but different from the results of Jin et al [10] that the size of the nanoparticles did not change after irradiation. It also can be seen that the shape of the excitation spectrum also changed.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…The radius of the ZnS nanoparticles before the irradiation was calculated to be 2.97 nm and after the irradiation the radius was reduced to 2.36 nm. This indicates that the irradiation resulted in the decreasing of the nanoparticles, as was reported by Bol et al [24], but different from the results of Jin et al [10] that the size of the nanoparticles did not change after irradiation. It also can be seen that the shape of the excitation spectrum also changed.…”
Section: Resultscontrasting
confidence: 79%
“…The other is that the UV light induced the polymerization of the methacrylic acid stabilizer, leading to a better surface passivation [4,18]. The third is that the UV curing made the surface of the nanoparticles photo-oxidated, which provided a more efficient passivation [24]. In this paper, Mn 2+ -doped ZnS nanoparticles were prepared in AOT micelles and the irradiation-induced luminescence enhancement effect was observed too.…”
Section: Introductionmentioning
confidence: 86%
“…In particular, the report on Mn 2+ -doped ZnS nanoparticles (the high PL efficiency and the short PL lifetime) stimulated considerable efforts [41]. However, almost studies showed that the lifetime shortening of the Mn 2+ luminescence does not occur: The strong sp-d wave function mixing model cannot explain the enhancement of luminescence intensity in ZnS:Mn nanoparticles [36,42,43]. It is likely that the origin of rapid emission in Ref.…”
Section: Impurity Doping and Impurity-doped Semiconductor Nanoparticlesmentioning
confidence: 99%
“…The impurity-doped nanoparticles have usually been fabricated by chemical synthesis methods such as coprecipitation, reverse micelles, and organometallic procedures [35,36,42,43,[57][58][59][60][61][62][63][64]. High-quality undoped II-VI semiconductor nanoparticles have been synthesized by high-temperature organometallic methods [6,13,14].…”
Section: Impurity Doping and Impurity-doped Semiconductor Nanoparticlesmentioning
confidence: 99%
“…have been used to modify the nanocrystal surface. UV light irradiation [17,18] was also shown to be effective in reducing surface defects via photooxidation and enhance the photoluminescent efficiency. However, there is still no effective way to control the segregation of the doped Mn ions in the water-soluble nanocrystals.…”
Section: Introductionmentioning
confidence: 99%